Kelayakan Usaha Tani Sawi dan Selada Hijau Sistem Hidroponik di Kelompok Tani Tunas Harapan - Sundari, Ristina Siti; Heryadi, D. Yadi; Nursamsi, Roni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The horticulture sub-sector is part of the agricultural sector that contributes to agriculture in Indonesia. Indonesia will encounter a populace blast. In 2021, it will be 272,229,372 individuals, and it is anticipated that in the next year, it will increase in the future. A few choices to foster plant wares that are currently growing, particularly ways of life in metropolitan regions, incorporate Metropolitan Cultivating (metropolitan horticulture). The improvement of metropolitan cultivating in Tasikmalaya City is not comparable to the execution of metropolitan cultivating in substantial urban communities. Practicality of vegetable aqua-farming. The examination strategy utilized is contextual investigation, directed by interview and documentation. Respondents are chiefs of tank-farming development in the Fishes Harapan rancher bunch utilizing the Purposive Testing technique. Specifically, the respondents are chosen based on the scientist's evaluation that the respondent is the best party to utilize as an examination test. Information investigation technique utilizing NPV IRR PP net B/C. The consequences of the review show that the business is practical to go on for the long haul because the positive NPV esteem is Rp. 557,059, and the IRR is something very similar, precisely 12% of the 12% loan fee; then, at that point, the net advantage is a net B/C worth of 1.4. The compensation period requires 2 years.